2020
DOI: 10.1007/s00438-020-01666-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-additive (dominance) effects of genetic variants associated with refractive error and myopia

Abstract: Genome-wide association studies (GWAS) have revealed that the genetic contribution to certain complex diseases is welldescribed by Fisher's infinitesimal model in which a vast number of polymorphisms each confer a small effect. Under Fisher's model, variants have additive effects both across loci and within loci. However, the latter assumption is at odds with the common observation of dominant or recessive rare alleles responsible for monogenic disorders. Here, we searched for evidence of non-additive (dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For example, Troponin T3 (Tnnt3) as well as the Coiled-Coil Domain Containing Protein 80 (CCdc80), Alpha-3-Catenin (Ctnna3), and the Polycomb Group Ring Finger Protein (Pcgf5) play critical roles in cardiac/myogenic cell lineages and are crucial for striated muscle contraction [ 42 – 46 ]. Additionally, Zinc Finger Matrin-Type 4 (Zmat4) and the Paternally Expressed Gene 10 (Peg10) are implicated in mammalian neurogenesis [ 47 , 48 ], suggesting that VPA treatment induces changes in chromatin accessibility that favor onset of cell differentiation. This notion is supported by the fact that VPA exposure led to a net loss of ATAC-seq peaks and hence decreased accessibility at 3923 loci (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Troponin T3 (Tnnt3) as well as the Coiled-Coil Domain Containing Protein 80 (CCdc80), Alpha-3-Catenin (Ctnna3), and the Polycomb Group Ring Finger Protein (Pcgf5) play critical roles in cardiac/myogenic cell lineages and are crucial for striated muscle contraction [ 42 – 46 ]. Additionally, Zinc Finger Matrin-Type 4 (Zmat4) and the Paternally Expressed Gene 10 (Peg10) are implicated in mammalian neurogenesis [ 47 , 48 ], suggesting that VPA treatment induces changes in chromatin accessibility that favor onset of cell differentiation. This notion is supported by the fact that VPA exposure led to a net loss of ATAC-seq peaks and hence decreased accessibility at 3923 loci (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Special neurons in the retina react to light and transmit it to the brain to produce vision ( Pozarickij et al, 2020 ; Creeden et al, 2021 ; Liu H. et al, 2021 ; Yu et al, 2021 ; Elkhalifa et al, 2022 ). When neurons in the retina stop working properly, the eye can’t work properly.…”
Section: Nervous System-based Clinical Researchmentioning
confidence: 99%
“…Myopia development involves complicated gene-gene and geneenvironmental interactions that display high heterogeneity, with non-uniform, non-linear, and non-additive effects [129]. Establishing polygenic risk scores (PRS) with acceptable accuracy still requires a large amount of genetic, environmental, and ophthalmic data [141]. Nevertheless, a trio-based study of early-onset high myopia using next-generation sequencing and whole-exome sequencing (WES) suggested that de novo mutations of the BSG gene may play a causative role in myopia and may therefore serve as genetic predictors [142].…”
Section: Prevention Of Myopia Onsetmentioning
confidence: 99%
“…A study that screened the known variants associated with refractive error for nonadditivity (dominance) showed that non-additive effects had negligible impacts on the accuracy of a PRS for refractive error derived by using genome-wide significant GWAS variants [141]. In another recent genetic association study of 54,006 individuals, PRSs derived from a GWAS for high myopia were predictive of high myopia, low myopia, and hyperopia [151].…”
Section: Polygenic Risk Scores: Prediction For Early Interventionmentioning
confidence: 99%